2021
DOI: 10.3389/fphys.2021.678838
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei Strain Shirota Enhances the Ability of Geniposide to Activate SIRT1 and Decrease Inflammation and Oxidative Stress in Septic Mice

Abstract: Gardenia jasminoides Ellis is rich in geniposide, which can be transformed into the anti-oxidant and anti-inflammatory agent genipin. Genipin exhibits greater efficacy than geniposide, but it is unstable and difficult to preserve. In this study, a mouse model for sepsis was established by cecal ligation and puncture, and then we explored the effects and mechanism of Lactobacillus casei strain Shirota (LcS) on the enhancement of the ability of geniposide to reduce sepsis and decrease inflammatory and oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…One of the goals that ensure continued Pharmaceutical Services is to secure patient satisfaction for services provided by either the pharmacist or the pharmacist’s clinical. Two studies [ 69 , 70 ] showed that all the patients considered counseling as an important service and were satisfied with it and how pharmacist with skills in pharmaceutical care and counseling could be useful in promoting the service and making it profitable for the pharmacy business as shown too in this study that all the participants had a positive perception of the pharmaceutical care services.…”
Section: Study Resultsmentioning
confidence: 54%
“…One of the goals that ensure continued Pharmaceutical Services is to secure patient satisfaction for services provided by either the pharmacist or the pharmacist’s clinical. Two studies [ 69 , 70 ] showed that all the patients considered counseling as an important service and were satisfied with it and how pharmacist with skills in pharmaceutical care and counseling could be useful in promoting the service and making it profitable for the pharmacy business as shown too in this study that all the participants had a positive perception of the pharmaceutical care services.…”
Section: Study Resultsmentioning
confidence: 54%
“…In fact, geniposide is hydrolyzed to genipin via the action of β-glucosidase produced by intestinal or fecal microbiota, and the in vitro enzymatic treatment of GF extract also improves its bioactivity [ 14 , 20 ]. Thus, some studies have reported that a combination of geniposide or GF extract with Lactobacillus strains enhanced their functional properties, such as anti-oxidative stress and anti-inflammation in septic mice, an antioxidant effect in mouse liver injury, and an anti-proliferative effect in oral cancer cells [ 21 , 22 , 23 , 24 , 25 ]. Meanwhile, other studies have succeeded in enhancing the concentration of genipin using the immobilized bacterial enzyme glycosyl hydrolase family 3 β-glucosidase from L. antri or using immobilized fungal cells of Trichoderma reesei [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study suggested that Limosilactobacillus fermentum XJC60 could enhance mitochondrial capabilities, decrease ROS content in UV-damaged skin cells, and, therefore, keep the skin status [ 108 ]. In addition, new research has indicated antioxidant effect as the primary pathway by which Lacticaseibacillus rhamnosus GG (ATCC 53103, LGG) [ 109 ] and Lacticaseibacillus casei strain Shirota improve skin photoaging [ 110 ].…”
Section: Potential Mechanisms Of Probiotic-mediated Regulation Of Ski...mentioning
confidence: 99%